The distortion–push mechanism for the γ subunit rotation in F 1 -ATPase - Masahiro Motohashi; Mao Oide; Chigusa Kobayashi; Jaewoon Jung; Eiro Muneyuki; Yuji Sugita (Proceedings of the National Academy of Sciences, 2025)
F 1 -ATPase comprises the stator ring consisting of α 3 β 3 subunits and the rotor γ subunit. The γ subunit rotation mechanism has been extensively investigated by biochemical analyses, structural studies, single-molecule measurements, and computational studies. Recent cryoelectron microscopy (cryo-EM) structures of F 1 -ATPase from the thermophilic bacterium Bacillus PS3 (TF 1 ) provide us with further possibilities for a better understanding of the γ-rotation mechanisms. Using cryo-EM structures having the γ-rotation angles close to the binding dwell and catalytic dwell states, we investigate the relationships between the γ subunit rotation, conformational changes of the stator α 3 β 3 subunits, and the nucleotide-binding and release. We performed targeted molecular dynamics (MD) simulations with external forces on the α 3 β 3 subunits and observed 80° substep rotations of the γ subunit. Then, we optimized the most probable transition pathway through the mean-force string method simulations with 64 images. Finally, using umbrella sampling, we calculated the potential of mean forces along the minimum free energy pathway during the 80° substep rotation. Our MD simulations suggest that 80° substep rotation is divided into the first rotation, resting, and the second rotation. Notably, the first rotation is driven by the distortion of the stator α 3 β 3 subunits, and the second rotation is induced mainly by direct β/γ subunit interactions. This model, which we call the distortion–push mechanism, is consistent with the residue-level experimental analysis on F 1 -ATPase and the atomic structures determined by X-ray crystallography and cryo-EM.